Hubungan Lingkar Perut dan Lingkar Pinggul dengan Tekanan Darah pada Pegawai Fakultas Kedokteran Universitas Sam Ratulangi Manado - Erro, Maria M. (e-Biomedik, 2019)
Abstract: Increased abdominal circumference and hip circumference will potentially increase blood pressure. Blood pressure can be used as an indicator to assess the cardiovascular system. This study was aimed to determine the relationship between waist circumference as well as hip circumference and blood pressure among employees at Faculty of medicine Sam Ratulangi University Manado. This was an analytical study with a cross sectional design. Samples were obtained by using the accidental sampling method. Measurements of abdominal circumference, hip circumference and direct blood pressure were performed on all subjects. Data were analysed univariately and bivariately using the Pearson test. The results showed that there were 30 employees as subjects consisted of 17 males and 13 females. The mean of abdominal circumference and hip circumference in males and females were 80.03 ± 11.14 cm and 83.76 ± 12.61 cm consecutively. There were 33.3% of the employees that had high blood pressure (hypertension). In male employees, there was a moderate significant correlation between hip circumference and diastolic blood pressure (r=0.48; P=0.004) meanwhile in female employees there was a moderate significant correlation between waist circumference and systolic blood pressure (r=0.489; P=0.006). Conclusion: There was a significant relationship between hip circumference and diastolic blood pressure among male employees as well as between waist circumference and systolic blood pressure among female employees.Keywords: waist hip circumference ratio, blood pressureAbstrak: Peningkatan lingkar perut dan lingkar pinggul berpotensi meningkatkan tekanan darah. Tekanan darah dapat dipakai sebagai indikator untuk menilai sistem kardiovaskular. Penelitian ini bertujuan untuk mengetahui hubungan lingkar perut dan lingkar pinggul dengan tekanan darah pada pegawai Fakultas Kedokteran Universitas Sam Ratulangi Manado. Jenis penelitian ialah observasional. Sampel diperoleh dengan menggunakan metode accidental sampling dari pengukuran lingkar perut, lingkar pinggul, dan tekanan darah langsung. Analisis data menggunakan univariat dan bivariat dengan uji Pearson. Hasil penelitian mendapatkan sebanyak 30 orang pegawai sebagai subyek penelitian, terdiri dari 17 laki-laki dan 13 perempuan. Rerata lingkar perut dan lingkar pinggul pada laki-laki dan perempuan ialah 80,03±11,14 cm dan 83,76±12,61 cm. Sebesar 33,3% pegawai memiliki tekanan darah tinggi (hipertensi). Pada subyek laki-laki terdapat korelasi sedang dan bermakna antara lingkar pinggul dan tekanan darah diastolik (r=0,48; P=0,004) sedangkan pada subyek perempuan terdapat korelasi sedang dan bermakna antara lingkar perut dengan tekanan darah sistolik (r=0,489; P=0,006). Simpulan: Pada laki-laki terdapat hubungan bermakna antara lingkar pinggul dan tekanan darah diastolik sedangkan pada perempuan terdapat hubungan bermakna antara lingkar perut dengan tekanan darah sistolik.Kata kunci: RLPP, tekanan darah